Estimation of the photometric redshift of galaxies using artificial neural networks - Brito, Sofia; Sobreira, Flávia (Cadernos de Astronomia, 2026)
This work was presented at the event "The Astro-Scientists: III Brazilian Meeting of Girls and Women in Astrophysics, Cosmology and Gravitation", held between March 31 and April 4, 2025.